DNA ploidy index in gastric cancer and its relationship with tumor localization and histologic findings - Abdulhalim BAKİ and Yavuz TEKELİOĞLU and Abdulkadir REİS and Mehmet SARI and Sait KAPICIOĞLU (Turkish Journal of Gastroenterology, 2019)
-